Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1017/s1092852923002225
|View full text |Cite
|
Sign up to set email alerts
|

Digital health technologies and major depressive disorder

Abstract: There is an urgent need to improve the clinical management of major depressive disorder (MDD), which has become increasingly prevalent over the past two decades. Several gaps and challenges in the awareness, detection, treatment, and monitoring of MDD remain to be addressed. Digital health technologies have demonstrated utility in relation to various health conditions, including MDD. Factors related to the COVID-19 pandemic have accelerated the development of telemedicine, mobile medical apps, and virtual real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 119 publications
(220 reference statements)
0
7
0
Order By: Relevance
“…Due to the non-availability of in-person services, self-management skills become more important for patients as users of digital mental health care ( 20 , 53 ). From patients' perspectives, our result showed that DTx could be a tool to improve coping with major depression for a period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the non-availability of in-person services, self-management skills become more important for patients as users of digital mental health care ( 20 , 53 ). From patients' perspectives, our result showed that DTx could be a tool to improve coping with major depression for a period.…”
Section: Discussionmentioning
confidence: 99%
“…Participants perceive DTx a reliable source of information, but apart from that appraise them as less effective than face-to-face psychotherapy. Even though DTx are not perceived as a substitute, research shows comparable effects of digital interventions and face-to-face treatment ( 20 , 54 ), but reliable evaluations for digital mental health interventions are not comprehensive ( 20 , 55 ). According to the admission process, permanently listed DTx fulfilled higher evaluation standards ( 24 ) to examine effectiveness and contribute to evidence-based mental health care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CBT and mindfulness can be conducted by a chatbot in an app or by a therapist online. 15 , 28 , 33 , 34 Additionally, as digital health technology interventions are effective for eating disorders, 35 online and app-based dietary approaches may become more extensively used in the future. Furthermore, organizational efforts are important for mental health, 36 and interventions such as psychological safety (eg, crew resource management 37 ) may be offered via apps in the future.…”
Section: Systematization Of Digital Health Technologies and Proposalmentioning
confidence: 99%
“…Digital biomarkers, collected through digital devices, offer objective and quantifiable physiological and behavioral data. They enable remote data collection, potentially reducing the burden of in-clinic visits and providing insights into clinically relevant changes (McIntyre et al, 2023 ). Wearable technologies and smartphone apps contribute to digital phenotyping, allowing for moment-by-moment assessment of individual characteristics in real-world environments.…”
Section: Introductionmentioning
confidence: 99%